Never Mind the Trolley The Ethics of Autonomous Vehicles in Mundane Situations - Himmelreich, Johannes (Ethical theory and moral practice, 2018)
Trolley cases are widely considered central to the ethics of autonomous vehicles. We caution against this by identifying four problems. (1) Trolley cases, given technical limitations, rest on assumptions that are in tension with one another. Furthermore, (2) trolley cases illuminate only a limited range of ethical issues insofar as they cohere with a certain design framework. Furthermore, (3) trolley cases seem to demand a moral answer when a political answer is called for. Finally, (4) trolley cases might be epistemically problematic in several ways. To put forward a positive proposal, we illustrate how ethical challenges arise from mundane driving situations. We argue that mundane situations are relevant because of the specificity they require and the scale they exhibit. We then illustrate some of the ethical challenges arising from optimizing for safety, balancing safety with other values such as mobility, and adjusting to incentives of legal frameworks.